2020
DOI: 10.1177/0300060520951649
|View full text |Cite
|
Sign up to set email alerts
|

CD14, CD163, and CCR1 are involved in heart and blood communication in ischemic cardiac diseases

Abstract: Objective Cardiac diseases lead to heart failure (HF), but the progression can take several years. Using blood samples to monitor changes in the heart before clinical symptoms begin may help to improve patient management. Methods Microarray data GSE42955 and GSE9128 were used as study datasets and GSE16499, GSE57338, and GSE59867 were used as validation groups. The “limma” package from R Language was used to identify differentially expressed genes. Functional enrichment analyses of gene ontology terms and Kyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…CTSG (cathepsin G) is a protein coding gene plays important roles in aortic aneurysms [ 166 ]. Evidence from Safa et al [ 167 ], Chen et al [ 168 ], Zhou et al [ 169 ], Hu et al [ 170 ], Lou et al [ 171 ], Zhang et al [ 172 ] and Chen et al [ 173 ] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [ 174 ] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…CTSG (cathepsin G) is a protein coding gene plays important roles in aortic aneurysms [ 166 ]. Evidence from Safa et al [ 167 ], Chen et al [ 168 ], Zhou et al [ 169 ], Hu et al [ 170 ], Lou et al [ 171 ], Zhang et al [ 172 ] and Chen et al [ 173 ] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [ 174 ] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the dynamic progression of HF, heart samples is the best straightforward to monitor this progression [4]. Herein, we con rmed our computational analysis using qRT-PCR in left ventricle and peripheral blood specimens to follow probable dynamic mRNA expression being consistent with ICM progression from CAD and MI phenotypes.…”
Section: Discussionmentioning
confidence: 65%
“…M2 macrophages inhibit tumor apoptosis and activate NK-κB to triggers cell proliferation releasing proangiogenic factors such as VEGF, FGF2 and TNFα and immunomodulatory factors such as IL-10 and TGF-β [28]. The immune and in ammatory responses are critical biochemical processes in ischemic heart failure [4]. From the above, there are reasonable hypothesis that disrupted in ammatory responses relevant to CD163 is strongly nominated to be key biomarker in ischemic heart failure progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[158], Chen et al [159], Zhou et al [160], Hu et al [161], Lou et al [162], Zhang et al [163] and Chen et al [164] study indicated that the expression of CCL22, CCR1, FPR1, KNG1, CRISPLD2, CD38 and GPRC5A were linked with progression of ischemic heart disease. Li et al [165] showed that STEAP3 expression can be associated with cardiac hypertrophy progression.…”
Section: Discussionmentioning
confidence: 99%